Characterisation of Microparticle Waste from Dental Resin-Based Composites - Jesus Ojeda Ledo (Materials, 2021)
Clinical applications of resin-based composite (RBC) generate environmental pollution in the form of microparticulate waste. Methods: SEM, particle size and specific surface area analysis, FT-IR and potentiometric titrations were used to characterise microparticles arising from grinding commercial and control RBCs as a function of time, at time of generation and after 12 months ageing in water. The RBCs were tested in two states: (i) direct-placement materials polymerised to simulate routine clinical use and (ii) pre-polymerised CAD/CAM ingots milled using CAD/CAM technology. Results: The maximum specific surface area of the direct-placement commercial RBC was seen after 360 s of agitation and was 1290 m2/kg compared with 1017 m2/kg for the control material. The median diameter of the direct-placement commercial RBC was 6.39 μm at 360 s ag-itation and 9.55 μm for the control material. FTIR analysis confirmed that microparticles were sufficiently unique to be identified after 12 months ageing and consistent alteration of the outermost surfaces of particles was observed. Protonation-deprotonation behaviour and the pH of zero proton charge (pHzpc) ≈ 5–6 indicated that the particles are negatively charged at neutral pH7. Conclusion: The large surface area of RBC microparticles allows elution of constituent monomers with potential environmental impacts. Characterisation of this waste is key to understanding potential mitigation strategies.